COMUNICAÇÃO MERCADOLÓGICA EM MÍDIAS SOCIAIS ONLINE ANÁLISES PARA RELACIONAMENTOS EM REDES VIRTUAIS - Bento, Laércio (2012)
With the purpose of increasing their marketing campaigns, many organizations turn to social media tools hosted on the Internet. With that, these organizations look for increased productivity by adopting automated message, or even feature direct access, entering characterized persuasive messages in discussion forums in online communities. It can be seen here certain lack of sensitivity to deal with communication, a medium in which the message is not necessarily an easy propagation environment. Often implies a possibility of reverberation indicating greater attention be essential in the development and direction of these communications flows, for the purposes sharply persuasive. Accordingly, this paper proposes the study of online communities in which we, from the identification of factors that lead to the formation of these communities, analyse and interpret its structure and communications flows, such that its elements indicate aggregators. To this end, we aim to demonstrate that with these components, the analysis can be developed to better match strategies relationships, enabling actions inherent in the marketing communication process with these communities. The network structure was analyzed with software applications such as integration with UCINET NetDraw, and communication flows formed the corpora analyzed with Wordsmith Tools suite. A network formed in the community hosted in orkut provided the corpora for lexical analysis. The obtained results could characterize not only the very existence of the social network, such as the potential relationship, from interpretations of dialogic flows of its elements aggregators, through visuals (graphs), statistical and lexical means.